Transmission of viable Haemophilus ducreyi by Musca domestica. - Haley D Stabile; Kayla McCandless; Rachel A Donlan; Jordan R Gaston; Tricia L Humphreys (Public Library of Science (PLoS), 2024)
Haemophilus ducreyi was historically known as the causative agent of chancroid, a sexually-transmitted disease causing painful genital ulcers endemic in many low/middle-income nations. In recent years the species has been implicated as the causative agent of nongenital cutaneous ulcers affecting children of the South Pacific Islands and West African countries. Much is still unknown about the mechanism of H. ducreyi transmission in these areas, and recent studies have identified local insect species, namely flies, as potential transmission vectors. H. ducreyi DNA has been detected on the surface and in homogenates of fly species sampled from Lihir Island, Papua New Guinea. The current study develops a model system using Musca domestica, the common house fly, as a model organism to demonstrate proof of concept that flies are a potential vector for the transmission of viable H. ducreyi. Utilizing a green fluorescent protein (GFP)-tagged strain of H. ducreyi and three separate exposure methods, we detected the transmission of viable H. ducreyi by 86.11% ± 22.53% of flies sampled. Additionally, the duration of H. ducreyi viability was found to be directly related to the bacterial concentration, and transmission of H. ducreyi was largely undetectable within one hour of initial exposure. Push testing, Gram staining, and PCR were used to confirm the identity and presence of GFP colonies as H. ducreyi. This study confirms that flies are capable of mechanically transmitting viable H. ducreyi, illuminating the importance of investigating insects as vectors of cutaneous ulcerative diseases.